Effect of fuel content and extra MgO on the formation of MgNb2O6 - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2012)
Urea combustion method was employed to produce MgNb2O6 columbite ceramic powders using MgCO3 and Nb2O5. The fuel content was varied as urea/metal cation ratio of 1 and 6 to observe the effect indicated that higher fuel content led to formation of MgNb2O6 phase at lower temperature. Higher fuel content together with excess MgO of 0.5wt% led to a decrease in the MgNb2O6 single of fuel content on phase formation. Extra MgO was added into the stoichiometric MgNb2O6 powder in order to elucidate the effect of excess MgO on phase formation and MgNb2O6 grain size. X-ray diffraction results phase formation temperature. SEM investigation revealed that only single phase was observed in sintered ceramics. SEM examination also indicated that excess MgO addition slightly decreased the MgNb2O6 grain size.
Keywords: Columbite ceramic; Combustion synthesis